Translation Strategy of Psychological Terms in the Book Thinking, Fast and Slow - Felicita Sonya, Anna Maria; Erni Hastuti; Teddy Oswari (Universitas PGRI Yogyakarta, 2025)
Translation is a process of rendering one meaning from source text into target text, consequently the translator is expected to understand both linguistically and culturally related to the target text comprehensively. This research aims to investigated how are strategies of translation applied in English psychological terms that translated into Indonesian, describing in detail the process of transferring meaning from the source text to the target text to obtain factual data and information related to the translation strategies and principles used by the translator. The method applied in this research is qualitative. The data are taken from the book by Daniel Kahneman entitled Thinking, Fast and Slow. The data are words and phrases that belong to psychological terms, then data were analysed using Andrew Chesterman translation strategies. Result of the research shows that from the data that have been collected, 8 out of 30 strategies is applied in the translation, that is literal translation 35 data, loan 2 data, calque 14 data, transposition 4 data, unit shift 10 data, emphasis change 3 data, paraphrase 8 data and cultural filtering (adaptation) 24 data. The most dominant strategy used in translating English psychological terms in Daniel Kahneman’s Thinking, Fast and Slow into Indonesian is literal translation.